Controls on Capital Inflows and the Transmission of External Shocks - David, Antonio C. (2012)
In this paper we attempt to analyse whether price-based controls on capital inflows are successful in insulating economies against external shocks. We present results from vector autoregressive (VAR) models, which indicate that Chile and Colombia, countries that adopted controls on capital inflows, seem to have been relatively well insulated against certain types of external disturbances. Subsequently, we use the autoregressive distributive lag (ARDL) approach to co-integration in order to isolate the effects of the capital controls on the pass-through of external disturbances to domestic interest rates in those economies. We conclude that there is evidence that the capital controls have allowed for greater policy autonomy.